Developing a Waste Management Start-Up as Efforts to Accelerate the Circular Economy: Pengembangan Start-Up Pengelolaan Sampah Sebagai Upaya Akselerasi Ekonomi Sirkular - Rahmawati, Cut; Faisal, Muhammad; Sanusi, Sanusi; Muhtadin, Muhtadin; Miftahul Jannah; Abdus Salam; Muhammad Fatani (Universitas Lancang Kuning, 2024)
The purpose of developing this start-up is to organize the collection of waste in the community, in the form of plastic and glass waste. This waste will be managed at the Self-Realization Waste Bank to become new, more valuable products. Plastic waste will be shredded into smaller pieces and melted. The melted plastic will then be transformed into paving blocks. Meanwhile, glass waste will be crushed into artificial sand, which will also be used to make paving blocks. The collection of plastic waste and glass waste is organized through a web-based start-up that can be accessed by the general public. The method used involves socializing the program and practicing product manufacturing. The results of the activities show that partners can operate the developed start-up and can already create products from plastic waste and glass waste. Partners can also transform glass waste into artificial sand. Products produced from plastic waste and glass waste can be used as surface covers for pedestrian paths and parking areas.